Charitable giving for overseas development: UK trends over a quarter century - Anthony B. Atkinson; Peter G. Backus; John Micklewright; Cathy Pharoah; Sylke Viola Schnepf (Institute for the Study of Labor (IZA), 2008)
Charitable giving for overseas development and emergency relief is important in the UK, being about a quarter of the size of government development aid. There has been a strong growth over time, reflecting the activities of development charities and the public response to a series of humanitarian emergencies. This paper examines how individual overseas giving has changed over the quarter century since 1978, using a newly constructed panel data set on donations to individual UK charities. When did the increase take place? Did the public respond to events such as Live Aid? Or has there been a steady upward trend as our society became more globalised? What form did the increase in giving take? Which charities have grown fastest? Have new charities displaced old? How do changes in giving for overseas compare with changes in giving for other causes such as cancer relief or animal welfare? What, if any, is the relation with Official Development Assistance?
urn:nbn:de:101:1-2008121784
Keywords: D12; 330; Charitable giving; overseas development; philanthropy; UK; Entwicklungshilfe; Entwicklungsorganisation; Katastrophenhilfe; Wohltätigkeit; Großbritannien